2018
DOI: 10.1097/corr.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Dual Interlocking Telescopic Rod Provides Effective Tibial Stabilization in Children With Osteogenesis Imperfecta

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…15,[39][40][41] In all the years, despite improved surgical techniques and more sophisticated implants, the overall complication and reoperation rate has not changed a lot. 25,[27][28][29]31 The causes of failure have not changed either: distal and proximal rod migration, jamming of the telescoping mechanism, bending rods due to the operating mechanical and muscular forces and technical issues with the operation. 25,[27][28][29]31 Most of these problems are caused by the weak bones; the disease itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,[39][40][41] In all the years, despite improved surgical techniques and more sophisticated implants, the overall complication and reoperation rate has not changed a lot. 25,[27][28][29]31 The causes of failure have not changed either: distal and proximal rod migration, jamming of the telescoping mechanism, bending rods due to the operating mechanical and muscular forces and technical issues with the operation. 25,[27][28][29]31 Most of these problems are caused by the weak bones; the disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…25,[27][28][29]31 The causes of failure have not changed either: distal and proximal rod migration, jamming of the telescoping mechanism, bending rods due to the operating mechanical and muscular forces and technical issues with the operation. 25,[27][28][29]31 Most of these problems are caused by the weak bones; the disease itself. Despite of all these negative points the overall activity level of our patients with weak bones has clearly improved.…”
Section: Discussionmentioning
confidence: 99%
“…11 ). Then, the next-generation telescopic rods that facilitate antegrade insertion of the obturator without arthrotomy of the distal joint and without damage to the distal articular cartilage of the long bone were introduced, including the interlocking telescopic rod, 35 36) Fassier-Duval rod, 37) and cork-screw tipped telescopic rod 38) ( Figs. 12 and 13 ).…”
Section: Fixation Options For Fracture And/or Osteotomymentioning
confidence: 99%
“…In the current study, Shin and colleagues [6] took this concept further, advancing from the single-to a dual interlocking telescopic rod (D-ITR), by substituting the proximal fixed T-piece with an interlocking pin. The authors found no differences between these two systems in terms of mean surgery-free survival time, mean rod survival time, cessation of elongation, or elongated length.…”
mentioning
confidence: 99%
“…Surgeons should consider, in terms of epiphyseal damage and/or radiation exposure, the long distance that the interlocking pin must travel within the tibial epiphysis before it reaches the small hole in the rod. Although the authors state that "the procedure is less challenging than it may appear" [6], they also mention that "because of osteopenia of the typical OI epiphysis, the interlocking pin can be manipulated easily during insertion" [6]. Future studies should explore either the various specific design elements of the commercially available rods or the instruments for implanting these rods (such as guiding systems to help ensure correct placement of the interlocking pins), with the goal of mitigating complications.…”
mentioning
confidence: 99%